2012
DOI: 10.1371/journal.pone.0030150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Hydrostatic Pressure on Bacterial Growth on Human Ossicles Explanted from Cholesteatoma Patients

Abstract: BackgroundHigh hydrostatic pressure (HHP) treatment can eliminate cholesteatoma cells from explanted human ossicles prior to re-insertion. We analyzed the effects of HHP treatment on the microbial flora on ossicles and on the planktonic and biofilm states of selected isolates.MethodologyTwenty-six ossicles were explanted from cholesteatoma patients. Five ossicles were directly analyzed for microbial growth without further treatment. Fifteen ossicles were cut into two pieces. One piece was exposed to HHP of 350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…were isolated from 26 sputa, 9 nasal swabs, 9 tracheal secretions, 7 broncho-alveolar lavages, 7 pharyngeal swabs (3 of them from known mucoviscidosis patients), 6 eye swabs, 5 nasal secretions, 2 bronchial secretions, 2 ear swabs, 1 palatine swab, 1 ossicle fragment, 1 maxillary sinus swab, and 1 peritonsillar abscess (Table 1) in routine microbiological diagnostic analyses. One isolate, a H. parainfluenzae strain, was isolated in the course of a recent anonymized study [28] at the University of Rostock. Patient-related data associated with the bacterial isolates, i.e., age and sex of the patients, are not presented for ethical considerations.…”
Section: Methodsmentioning
confidence: 99%
“…were isolated from 26 sputa, 9 nasal swabs, 9 tracheal secretions, 7 broncho-alveolar lavages, 7 pharyngeal swabs (3 of them from known mucoviscidosis patients), 6 eye swabs, 5 nasal secretions, 2 bronchial secretions, 2 ear swabs, 1 palatine swab, 1 ossicle fragment, 1 maxillary sinus swab, and 1 peritonsillar abscess (Table 1) in routine microbiological diagnostic analyses. One isolate, a H. parainfluenzae strain, was isolated in the course of a recent anonymized study [28] at the University of Rostock. Patient-related data associated with the bacterial isolates, i.e., age and sex of the patients, are not presented for ethical considerations.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining single isolate, a H. parainfl uenzae isolate, was collected at the University of Rostock from an anonymous patient who visited the University of Rostock hospital complaining of an URT infection in the course of the study [36]. The 76 patients comprised 49 men and 27 women.…”
Section: Distribution Of Haemophilus Spp In Relation To Sex and Agementioning
confidence: 99%
“…Our previous study showed that HHP‐devitalized cartilage has still strong chondroinductive potential . Devitalization using HHP represents a gentle technique for cell inactivation while extracellular cartilage matrix is preserved . Therefore, devitalized cartilage may be an ideal scaffold for the repair of cartilage lesions.…”
Section: Discussionmentioning
confidence: 99%
“…17 Devitalization using HHP represents a gentle technique for cell inactivation while extracellular cartilage matrix is preserved. [29][30][31] Therefore, devitalized cartilage may be an ideal scaffold for the repair of cartilage lesions. In this pilot study, we investigated the feasibility of HHP-devitalized osteochondral plugs to repair osteochondral defects in a rabbit model over 12 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%